WHAT IS THE PURPOSE OF THE PUBLIC DEBT IN NORTH MACEDONIA - CURRENT, CAPITAL OR SOCIAL SPENDING - Beciragic, Ivana; Trenovski, Borce (International Journal of Economic Practice and Policy, 2024)
North Macedonia, as one of the small and open economies in the region, is facing an increase in the budget deficit and public debt (especially in the last couple of years), which, in conditions of reduced fiscal capacity, is increasingly emphasizing the issue of the distribution of funds from borrowing. The government’s intention is to increase public debt to generate investments in the infrastructure and create future benefits for the economy as a whole, as well as the potential for future debt recovery. But, is this really the case? In reality, capital expenditures are stagnating, while current budget expenditure and social transfers are constantly rising. This paper investigates the dynamics of the rise in public debt and the trends in capital expenditure, current expenditure, and social transfers. Furthermore, we explore the effects each category of social transfers (pensions, unemployment benefits, social assistance, and health insurance transfers) has on the level of public debt in the country. We employ a VARMAX model on quarterly data from 2008 to the second quartile of 2022. The results of the VARMAX model show that a short-term increase follows the shock in public debt in the current budget expenditure. This suggests that the government has been increasing the public debt mostly to finance current budget expenditures instead of investing in economic and social infrastructure. In addition, the analysis of the relationship between the public  debt and the four different categories of social transfers shows that the shock in public debt is followed by a short-term increase in health insurance transfers.
Keywords: VARMAX model; public debt; social expediture; capital expenditure; current budget expenditures